Treat me rights : essays in medical law and ethics. - "Kennedy, IAN" (Oxford, 1988)
This book brings together a wide cross-section of the author's work in the field of medical law and ethics. Many of the articles have appeared previously in journals, but all are updated. Some are published here for the first time. Professor Kennedy, a former Reith Lecturer and a well-known scholar and broadcaster, writes not only authoritatively and informatively about the subject, but often in a way that is provocative, controversial, and amusing. It is a collection that will interest the lawyer with medico-legal interests, and the doctor who wants to know more about the rights, duties, and liabilities of his profession, the student of law or medicine, and the layperson who follows developments in this scientifically complex and morally contentious area of law.
Keywords: Medical laws and legislation -Great Britian